2020
DOI: 10.3389/fneur.2020.00563
|View full text |Cite
|
Sign up to set email alerts
|

Ablating Tau Reduces Hyperexcitability and Moderates Electroencephalographic Slowing in Transgenic Mice Expressing A53T Human α-Synuclein

Abstract: Abnormal intraneuronal accumulation of the presynaptic protein α-synuclein (α-syn) is implicated in the etiology of dementia with Lewy bodies (DLB) and Parkinson's disease with dementia (PDD). Recent work revealed that mice expressing human α-syn with the alanine-53-threonine (A53T) mutation have a similar phenotype to the human condition, exhibiting long-term potentiation deficits, learning and memory deficits, and inhibitory hippocampal remodeling, all of which were reversed by genetic ablation of microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
4
18
0
Order By: Relevance
“…However, the physiological roles of α-Syn in the non-motor symptoms of PD are yet to be fully elucidated. Consistent with the findings of a previous study [ 53 , 54 ], the present study showed that the mice did not show motor deficits in the grip strength test, hanging wire test, or cylinder test, but non-motor symptoms, such as anxiety and hyperactivity, were revealed in the mice, as shown by the open field test results in Figure 1 F,G.…”
Section: Discussionsupporting
confidence: 93%
“…However, the physiological roles of α-Syn in the non-motor symptoms of PD are yet to be fully elucidated. Consistent with the findings of a previous study [ 53 , 54 ], the present study showed that the mice did not show motor deficits in the grip strength test, hanging wire test, or cylinder test, but non-motor symptoms, such as anxiety and hyperactivity, were revealed in the mice, as shown by the open field test results in Figure 1 F,G.…”
Section: Discussionsupporting
confidence: 93%
“…Myoclonus can also be treated with levetiracetam (Caviness, 2014), thus it would be interesting to see if drugs aimed at reducing hyperexcitability could restore the changes in sleep-related oscillations we have observed as a result of the α-syn pathology in the A30P mouse model. Interestingly, epilepsy and myoclonus have recently been reported in A53T α-syn mice which was associated with reduced NREM sleep and more time spent in the awake state (Peters et al, 2020). Ours and other data, therefore, support the idea that early interventions aimed at improving sleep cycle regulation and sleep-related oscillations could be beneficial, not only in AD (Mander et al, 2016) and PD (Bohnen and Hu, 2019), but also in patients with DLB.…”
Section: The Clinical Significance Future Directions and Limitationssupporting
confidence: 79%
“…Using mice that over-express human wild-type α-syn to model DLB, a shift of power from higher alpha to lower theta frequencies was also found in awake mice (Morris et al, 2015), and during NREM and REM sleep (McDowell et al, 2014). Studies in transgenic α-syn mice which have also shown alterations in the sleep-wake cycle in awake-behaving animals (Rothman et al, 2013;McDowell et al, 2014;Peters et al, 2020). However, detailed studies of the SO and spindles in murine models of α-syn are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These events coincided with a leftward shift in baseline EEG power reflecting a greater proportion of low frequency activity ( Morris et al, 2015 ). When overexpression of a mutant transgene of α-synuclein (A53S) is combined in a mouse lacking endogenous tau, EEG-slowing induced by overexpression of α-synuclein is markedly attenuated, suggesting a clear link between these two proteins in seizure pathology witnessed in DLB ( Peters et al, 2020 ).…”
Section: Electroencephalographic Slowing and Hippocampal Hyperexcitab...mentioning
confidence: 99%